A simple analytical model for a fast 3D assessment of peripheral photon dose during coplanar isocentric photon radiotherapy - Sánchez-Nieto, Beatriz; López-Martínez, Ignacio N.; Rodríguez-Mongua, José Luis; Espinoza, Ignacio (Frontiers in Oncology, 2022)
As second cancers are an issue of growing concern in radiation oncology, accurate models that provide out-of-field dose to organ information are necessary. Several original publications offer different models, but perhaps with the desire to model the physics behind the behavior of the peripheral dose distributions, the models have turned out to be complex functions with too many parameters and are challenging to be implemented in the clinic. By partially sacrificing the idea of modeling the complex phenomena behind the scatter, transmission, and leakage (the so-called stray radiation), we have proposed a simple analytical model for fast estimation of peripheral photon dose in RT. The resulting model only has two parameters and requires minimum information from the associated RT plan so that it can be used not only prospectively (which could help to optimize the individual RT plan) but also retrospectively to feed the databases containing second cancer information, which now could be correlated to dose to organs. The latter will serve for parametrization of current second risk cancel models with data from a variety of radiotherapy treatments. The test for validating the model shows it as a promising model that performs with reasonable accuracy even in intensity-modulated treatments. Our peripheral dose model not only could have an enormous impact on second cancer modeling but in personalized radiotherapy by including the estimation of dose to distant organs. Not to say the importance of calculating the dose to the fetus of pregnant women underway radiotherapy, pace markers, etc.